Epidemiology and Clinical Management of Rheumatic Autoimmune Diseases in the COVID-19 Pandemic: A Review - Zhu, Yingzi; Zhong, Jixin; Dong, Lingli (Frontiers in Medicine, 2021)
The coronavirus disease 2019 (COVID-19) has been in pandemic for more than one year, with serious negative effects produced worldwide. During this period, there have been a lot of studies on rheumatic autoimmune diseases (RADs) combined with COVID-19. The purpose of this study is to review and summarize these experiences. Pubmed, Web of science, Embase and the Cochrane library were searched from January 15, 2020 to July 15, 2021 using RADs and COVID-19 related keywords. Based on a comprehensive review of studies covering 16 countries, the prevalence of COVID-19 does not necessarily increase in RADs patients compared to the general population. In RADs population infected with COVID-19, a high proportion of female patients (54.44% ~ 95.2%), elderly patients (≥50y, 48% ~75.88%), and patients with pre-existing comorbidities (respiratory, 4.8% ~ 60.4%; endocrine, 8.52% ~ 44.72%; cardiovascular, 15.7% ~ 64.73%) were observed, although this does not appear to have a decisive effect on disease severity. Many anti-rheumatic treatments have been extensively evaluated for their efficacy of treating COVID-19 in RADs patients, with TNF-α inhibitors and IL-6 receptor antagonist receiving more positive reviews. However, there is no conclusive information for most of the therapeutic regimens due to the lack of high-level evidence. Inflammatory markers or neutrophil-lymphocyte-ratio may be applied as indicators for clinical prognosis or therapeutic regimens adjustment. Thus, more research is still needed to address the prevalence, treatment and clinical monitoring of RADs patients in COVID-19 pandemic.